An approach to classifying human resources constraints to attaining health-related Millennium Development Goals - Wyss Kaspar (BMC, 2004)
Abstract Background For any wide-ranging effort to scale up health-related priority interventions, human resources for health (HRH) are likely to be a key to success. This study explores constraints related to human resources in the health sector for achieving the Millennium Development Goals (MDGs) in low-income countries. Methods and framework The analysis drew on information from a variety of publicly-available sources and principally on data presented in published papers in peer-reviewed journals. For classifying HRH constraints an analytical framework was used that considers constraints at five levels: individual characteristics, the health service delivery level, the health sector level, training capacities and the sociopolitical and economic context of a country. Results and discussion At individual level, the decision to enter, remain and serve in the health sector workforce is influenced by a series of social, economic, cultural and gender-related determinants. For example, to cover the health needs of the poorest it is necessary to employ personnel with specific social, ethnic and cultural characteristics. At health-service level, the commitment of health staff is determined by a number of organizational and management factors. The workplace environment has a great impact not only on health worker performance, but also on the comprehensiveness and efficiency of health service delivery. At health-sector level, the use of monetary and nonmonetary incentives is of crucial importance for having the accurate skill mix at the appropriate place. Scaling up of priority interventions is likely to require significant investments in initial and continuous training. Given the lead time required to produce new health workers, such investments must occur in the early phases of scaling up. At the same time coherent national HRH policies are required for giving direction on HRH development and linking HRH into health-sector reform issues, the scaling-up of priority interventions, poverty reduction strategies, and training approaches. Multisectoral collaboration and the sociopolitical and economic context of a country determine health sector workforce development and potential emigration. Conclusions Key determinants of success for achieving international development goals are closely related to human-resource development.